Ecological politics towards the protection of Alas Purwo National Park based on local wisdom - Setiawan, Eko; Sukesi, Keppi; Hidayat, Kliwon; Yuliati, Yayuk (Penerbit Universiti Kebangsaan Malaysia, 2023)
Alas Purwo National Park is a nature conservation area with a natural ecosystem located in Banyuwangi Regency, developed for recreational, educational and conservation purposes. Conservation area management requires an ecological political approach to examine each actor's role in natural resource management. In reality, policy makers have not been optimal in managing conservation areas because they are unable to implement policies properly. This research used a case study approach to analyze cases about the role of policy makers in implementing policies related to forest conservation. Data and documents collected in case studies from the Alas Purwo National Park Office. Data collection in this study is direct observation to the field, in-depth interviews, documentation. Data analysis using interactive models consists of three lines of activities, data reduction, data presentation, conclusions. In qualitative research, the whole process goes together. Findings showed that the ecological political approach used by Alas Purwo National Park policymakers views humans in nature as the source of all values. Forest resource management based on local wisdom must be placed in a management mechanism through socio-cultural institutional policies that have been rooted for generations. This interest is inserted into the national policy of local governments in the form of conservation area management. As an analytical knife to dissect this using a political ecology approach, in mapping problems and how to overcome them. Minimizing the risk of disasters and climate change because so far the local government and the community around the buffer village of the conservation area have not had sensitivity to the sustainability of natural resources. They only see it from the perspective of economic benefits without understanding that forests are deposits that must be preserved.